Estimating the marginal abatement costs of carbon dioxide emissions in China: A parametric analysis - Limin Du; Aoife Hanley; Chu Wei (Kiel Institute for the World Economy (IfW), 2013)
This paper investigates the technical inefficiency, shadow price and substitution elasticity of CO2 emissions of China based on a provincial panel for 2001-2010. Using linear programming to calculate a quadratic parameterized directional output distance function, we show that China's technical inefficiency increases over the period implying further scope for CO2 emissions reduction in the medium and longer term at best by 4.5% and 4.9% respectively. Our results (notwithstanding regional differences) highlight increases in the shadow price of CO2 abatement (1000 Yuan/ton in 2001 to 2100 Yuan/ton in 2010). Additionally, increasingly steep substitution elasticity highlights the difficult reality of reducing China's CO2 emissions.
Keywords: Q52; Q54; Q58; 330; CO2 emissions; Shadow Price; Parametric Estimation; China